First-Principle Calculations of Interfacial Resistance between Nickel Silicide and Hyperdoped Silicon with N-Type Dopants Arsenic, Phosphorus, Antimony, Selenium and Tellurium - Changmin Lim; Shinyeong Park; Jiwon Chang (Applied Surface Science Advances)
The interfacial resistance between NiSi2 and n-type doped Si was investigated using density functional theory calculations with hybrid functionals. We explored the resistance of Si at different doping concentrations by assigning an effective potential to each Si atom. Then, the valley filtering effect at the NiSi2/Si interface was estimated by comparing the transmission spectra of NiSi2 and Si. We also examined the interfacial resistance between NiSi2 and hyperdoped Si with substitutional n-type dopants, including pnictogen (P, As and Sb) and chalcogen (Se and Te) atoms. Two types of substitutional dopant structures (a single dopant and a dopant dimer) were considered. The formation and binding energies of a single P/Te and a P/Te dimer were investigated to understand the stability in Si. The resistances of Si with a single dopant and with a dopant dimer at high doping concentrations were calculated to show that the resistance as low as ∼ 4×10−11Ω·cm2 can be achieved with a single dopant (P, As and Sb). However, at high doping concentration where a dopant dimer forms, a P dimer cannot effectively donate electrons, resulting in high resistance, while a Te dimer can still provide electrons, achieving a resistance of ∼ 2×10−10Ω·cm2. Therefore, the chalcogen deep donor atoms (Se and Te) can be effective n-type donors and lower the silicide contact resistance at the interface where Si is extremely highly n-type doped.